A study of image colourfulness - Amati, Cristina; Mitra, Niloy J.; Weyrich, Tim (Cae 2014 - Proceedings of the Workshop on Computational Aesthetics - Joint Symposium on Computational Aesthetics and Sketch-Based Interfaces and Modeling and Non-Photorealistic Animation and Rendering, Expressive 2014, 2014)
Colourfulness is often thought of as a mere measure of quantity of colour, but user studies suggest that there are more factors influencing the perception of colourfulness. Boosting and enhancing colours are operations often performed for improving image aesthetics, but the relationship between colourfulness and aesthetics has not been thoroughly explored. By gathering perceptual data from a largescale user study we have shown how existing colourfulness metrics relate to it and that there is no direct linear dependence between colourfulness and aesthetics but correlations arise for different image categories such as: "landscape", "abstract" or "macro". 2014 Copyright held by the Owner/Author. Publication rights licensed to ACM. ACM 978-1-4503-3019-0/14/08.
CRIS-Team Scopus Importer:2022-07-26
Keywords: Aesthetics; Colourfulness; Crowd-sourced user study; Perception